2012
DOI: 10.1021/ja303204m
|View full text |Cite
|
Sign up to set email alerts
|

Optically Active, Amphiphilic Poly(meta-phenylene ethynylene)s: Synthesis, Hydrogen-Bonding Enforced Helix Stability, and Direct AFM Observation of Their Helical Structures

Abstract: Optically active, amphiphilic poly(meta-phenylene ethynylene)s (PPEa) bearing L- or D-alanine-derived oligo(ethylene glycol) side chains connected to the backbone via amide linkages were prepared by microwave-assisted polycondensation. PPEa's exhibited an intense Cotton effect in the π-conjugated main-chain chromophore regions in various polar and nonpolar organic solvents due to a predominantly one-handed helical conformation stabilized by an intramolecular hydrogen-bonding network between the amide groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
110
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 154 publications
(47 reference statements)
9
110
0
Order By: Relevance
“…A variety of assembled structures can be formed through covalent linkages between π-conjugated units (Figure 1b). Flexible linkers enable intramolecular folding, and the resulting folded molecules can adopt unique morphologies such as fibers [20][21][22] and two-dimensional nanosheets. 23 Conjugated linkers extended the π-conjugation length and the conjugated polymers can form nanofibers through their strong π-π interactions.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of assembled structures can be formed through covalent linkages between π-conjugated units (Figure 1b). Flexible linkers enable intramolecular folding, and the resulting folded molecules can adopt unique morphologies such as fibers [20][21][22] and two-dimensional nanosheets. 23 Conjugated linkers extended the π-conjugation length and the conjugated polymers can form nanofibers through their strong π-π interactions.…”
Section: Introductionmentioning
confidence: 99%
“…18−26 Throughout this time, novel, helical macromolecular scaffolds have emerged including systems such as oligio- 27 and poly(m-phenylene ethynylenes), 28,29 polyisocyanates, 30,31 polyisocyanides, 32−34 poly-(phenyl acetylenes), 35,36 poly(quinaxoline-2,3-dials), 37,38 and polycarbodiimides 39 to name a few. Polycarbodiimides, a relatively young class of helical macromolecules, have been an intense area of interest in the Novak group since the discovery of the controlled "living" Ti(IV)-mediated polymerization of carbodiimides in 1994 due to their attractive properties such as liquid crystallinity, 40,41 high helical inversion barrier, 42 and chiroptical switching.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Yashima and coworkers previously reported that poly(meta-phenylene ethynylene)s bearing L-alanine-derived oligo(ethylene glycol) side chains ((S)-PPEa) had a preferred-handed helical conformation induced by the covalent bonding of chiral alanine pendants, even in CHCl3 [38]. In CHCl3, the helical conformation of (S)-PPEa is likely to be stabilized by intramolecular hydrogen bonds between nonadjacent amide pendants [38].…”
Section: Chiroptical Properties In Dilute Solutionmentioning
confidence: 99%